The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/antiox10122025
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Dynamic Changes in the In Vitro Antioxidant Activity of Carob Kibbles upon Roasting to the Chemical and Structural Changes Revealed by FTIR Spectroscopy

Abstract: Recent studies have highlighted the potential of utilizing carob kibbles as a bioactive-rich food ingredient associated with substantial health benefits. Roasting is a key process in enhancing the sensory characteristics of carob kibbles, also affecting the bioactive polyphenols and leading to the formation of Maillard reaction products (MRPs), including the polymeric melanoidins that are associated with a high antioxidant potential but remain unexplored in carob. In this work, we employed for the first time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Comparing the Maillard reaction products and the TPC content of seaweeds, it can be observed that, particularly for E. bicyclis , there is an increase in the TPC content in fraction 3 that can be positively related to AGEs present in this fraction ( Table 2 ) [ 43 ]. According to Plaza et al [ 43 ] and Grigoriou and Pinakoulaki [ 53 ], besides phenolics, there are other classes of compounds that positively react with Folin–Ciocalteu reagent due to the presence of reducing groups. One example is the Maillard reaction products.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the Maillard reaction products and the TPC content of seaweeds, it can be observed that, particularly for E. bicyclis , there is an increase in the TPC content in fraction 3 that can be positively related to AGEs present in this fraction ( Table 2 ) [ 43 ]. According to Plaza et al [ 43 ] and Grigoriou and Pinakoulaki [ 53 ], besides phenolics, there are other classes of compounds that positively react with Folin–Ciocalteu reagent due to the presence of reducing groups. One example is the Maillard reaction products.…”
Section: Resultsmentioning
confidence: 99%
“…FT-IR analysis was conducted with an FT-IR attenuated total reflection (ATR) spectrometer (Thermo Scientific, Waltham, MA, USA). Spectra records were kept at a resolution between 400 and 4000 cm −1 for 64 scans [21].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir) Analysismentioning
confidence: 99%
“…Thermal processes can cause changes in the chemical composition, structure of compounds, and the bioactive properties of food. For example, roasting affects the qualitative and quantitative composition of polyphenols, the formation of Maillard reaction products and, consequently, the antioxidant potential of carob kibbles [ 6 ]. Thermal treatment also causes the degradation of anthocyanins, flavonoids, and other polyphenols and reduces the antioxidant activity of the red grape skin extract to a degree depending on the process parameters used (time, temperature) [ 7 ].…”
Section: Bioactive Compounds In Technological Processes Of Food Produ...mentioning
confidence: 99%